Chronology and documentary handbook of the State of Colorado. - Frech, Mary L. (Chronologies and documentary handbooks of the States, 1973)
Includes a chronology of events in Colorado from 1706 to 1971, a biographical directory, an outline of the state constitution, and selected documents.